Answer:
The solution of the equation is x = -9
Explanation:
∵ The equation is 6(x - 6) + 6 = 8x - 12
→ Use the distributive property to simplift the left sid
∵ 6(x - 6) = 6(x) - 6(6) ⇒ Distributive property
∴ 6(x - 6) = 6x - 36
∴ 6x - 36 + 6 = 8x - 12
→ Add the like terms in the left side
∴ 6x + (-36 + 6) = 8x - 12
∴ 6x + (-30) = 8x - 12
∴ 6x - 30 = 8x - 12
→ Subtract 8x from both sides
∴ 6x - 8x - 30 = 8x - 8x - 12
∴ -2x - 30 = -12
→ Add 30 to both sides
∴ -2x - 30 + 30 = -12 + 30
∴ -2x = 18
→ Divide both sides by -2
∵
![(-2x)/(-2)=(18)/(-2)](https://img.qammunity.org/2021/formulas/mathematics/high-school/u4w6u8ydoh9jgdbxbu7s88be2qgqx71608.png)
∴ x = -9
∴ The value of x is -9